METAGENOMIC APPROACH FOR MICROBIAL DIVERSITY IN ENVIRONMENTAL SAMPLES - KAUSTUBH SONKUSALE; VIDYA TALE (International Journal of Pharma and Bio Sciences, 2013)
The metagenomics is called as fourth domain of life which deals with the molecular approach for the culturing of the microbes. The development of metagenomics stemmed from the evidence that as-yet-uncultured microorganisms represent the vast majority of organisms in most environments on earth. These microbes hold the secret for generating renewable biofuels and bioremediation. This report throws light metagenomic approach of soil, water; methodologies involved in it and reported prevalent microbes in the above environmental niche. The importance of the bacteria in drug design, drug delivery and important products obtained from them by using the culturing technique called as Metagenomics.